Cockles shell as heterogeneous catalyst for biodiesel production from jatropha seed oil / Norulakmal Nor Hadi... [et al.] - Nor Hadi, Norulakmal; Ismail, Syazwan; Mohd. Salleh, Marmy Roshaidah; Ghafar, Faridah (Universiti Teknologi MARA, Perlis, 2016)
Cockles shell currently found to be a potential alternative and biomass-driven source for calcium oxide (CaO). It fits to be the best candidate as the alternative material as they are made up of at least 95% of calcium carbonate (CaCO3). In this research, biodiesel production by transesterification of crude Jatropha curcas oil (CJCO) has been studied using a cockle shell as a heterogenous catalyst. The calcium oxides; heterogeneous catalyst were produced from the calcination process of cockles shell at various temperature range from 600 to 800C. Different catalyst dosage have been used during the transesterification process. The amounts of catalyst added were varied from 0.5 wt% until 2.0 wt%. It was found that 94% of conversion was achieved when 1.5 wt % of 700 °C calcination temperature catalyst was added into the transesterification process. The component of fatty acids profiles contain within the biodiesel from CJCO were obtained using gas chromatography (GC) and found to be significant with the standard fatty acid methyl ester (FAME). The physical properties analysis results indicated that the value of flash point, relative density and kinematic viscosity were within the range of American Society for Testing and Materials (ASTM) standard for biodiesel.